Real-World Data and Budget Impact Analysis (BIA): Evaluation of a Targeted Next-Generation Sequencing Diagnostic Approach in Two Orthopedic Rare Diseases - Pedrini, Elena; Negro, Antonella; Di Brino, Eugenio; Pecoraro, Valentina; Sculco, Camilla; Abelli, Elisabetta; Gnoli, Maria; Magrelli, Armando; Sangiorgi, Luca; Cicchetti, Americo (Frontiers in Pharmacology, 2022)
Objective: Next Generation Sequencing (NGS) technology, changing the diagnostic approach, has become essential in clinical and its adoption by public health laboratories is now the practice. Despite this, as technological innovations, its intake requires an evaluation of both the clinical utility and the economic investment, especially considering the rare diseases scenario. This study evaluated the analytical validity and the budget impact of an NGS-Ion Torrent™ approach for the molecular germline diagnosis of two musculoskeletal rare diseases. Methods: Two cohorts of 200 and 199 patients with suspect or clinical diagnosis of Multiple Osteochondroma (MO) and Osteogenesis Imperfecta (OI) previously evaluated with a single-gene diagnostic protocol, were re-analyzed using a targeted NGS assay. Analytical validity was assessed by comparing NGS and single-gene protocol. A Budget Impact analysis using real-world cost data - considering the healthcare perspective - was performed applying the Activity Based Costing (ABC). Cost considered consumables, personnel, and equipment. Additional costs not related to NGS activities were not considered. Sensitivity analysis was performed. Results: The NGS method showed a higher (for MO) and comparable (for OI) diagnostic sensitivity compared to the traditional techniques, besides always reducing the time and costs of diagnosis. Overall, the per-patient saving is € 765 for OI and € 74 for MO. Materials represented the highest cost driver of the NGS process. A saving time - proportional to the panel size - has been assessed in both cases. Conclusions: Our targeted NGS diagnostic approach decreases time to diagnosis and costs, appearing to be beneficial and recommended both for patients and health care perspective in routine diagnosis also considering very small gene panels and a low patient flow. The adequate analytical sensitivity always required the additional Sanger sequencing step of the low- and no-covered regions. A more accurate strategy evaluation is suggested in the case of ultra-rare/complex diseases, large gene-panel, or non-reference diagnostic centers.